Os peixes da família Sternoptychidae (Teleostei, Stomiiformes) do talude e plataforma continental brasileira entre 11ºS e 23ºS - Lima, Adriano Truffi (2005)
There are very few mesopelagical samples accomplished in Brazilian waters. most of it are limited exclusively at south and southeast regions. As a consequence of it, the knowledge of the Brazilian Stemoptychidae is very limited, based on the material obtained by a few oceanographic cruises that took place in this area, of these the most important are the French RIV Marion Dufresne on the Trindade-Vitória ridge and the Brazilian R/V Atlantico Sul at southem Brazil. More recently, the most representative collection of Stemoptychidae known from the Southwest Atlantic was obtained. It was obtained, by four deep sea trawl cruises (pelagic and bottom) over the Brazilian continental shelf, slope and sea mounts between lIaS and 23°S (Babia 1 e lI; Oceanprof 1 e 11). These samples produced 12.710 specimens of Stemoptychidae, which were analyzed in the present work. Based on this collection, the following nine species were identified: Argyripnus atlanticus, Argyropelecus aculeatus. A. hemigymnus, A. sladeni. Maurolicus stehmanni, Sternoptyx diaphana, S. pseudodiaphana, S. pseudobscura e Polyipnus laternatus. Ofthese, Argyripnus atlanticus, Polyipnus laternatus e Sternoptyx pseudodiaphana are new records for Brazilian waters. Were also new the occurrence of the genera Argyripnus at South Atlantic and Polyipnus at Southwet Atlantic.